Analysis of the Influence of School Principal Leadership Style on Teacher Discipline in Integrated Private Schools - A. Dara Dewi Mallarangan; Didik Widiantoro; Ernawati Ernawati; Sehan Rifky; Miftahul Ulum (Departement of Mathematics Education, 2024)
The objective of this study is to investigate the potential correlation between the principal's democratic leadership style and teacher discipline. The researchers employed a quantitative research methodology characterized by a descriptive approach. The research population consisted of all teachers, and a sample of 100 teachers was randomly selected using sampling techniques. To gather data, the author employed various methodologies, including questionnaires, documentation analysis, and interviews. The data analysis was conducted utilizing quantitative methodologies and statistical instruments. The data indicates a favorable impact of the principal's democratic leadership on teacher discipline. Moreover, the partial test indicates that the t-count value is 3.5, surpassing the t-table value. Therefore, it can be inferred that the principal's democratic leadership has a substantial impact on teacher discipline. Furthermore, research findings demonstrate that school principals' inclination towards democratic leadership and teacher discipline falls within the moderate range. Hence, the democratic leadership style of the school principal has a substantial influence on the degree of teacher discipline.